Caracterização molecular do banco ativo de germoplasma de bromélias - Vieira, Sylvia Dantas (2013)
The bromeliad family comprises about 3,000 species distributed in 58 genera and 3 subfamilies: Pitcarnioideae, Bromelioideae and Tillandsioideae. The increasing demand of the market has been responsible for increasing the production and sale of bromeliads. However the illegal extraction is still dramatically reducing existing species. This fact, coupled with the devastation of Brazilian ecosystems, has caused irreparable losses in diversity. Considering this fact, have a basis with stored genetic material for future studies is very important. The main reason for the establishment and maintenance of a germplasm bank is to store and make available germplasm and provide information regarding certain accessions. The aim of the work was to perform the molecular characterization of accessions of native bromeliads prospected in Sergipe State, using tools such as RAPD and ISSR molecular markers and flow cytometry. The collections were performed in four counties of the Sergipe state (Itabaiana, Frei Paulo, Simão Dias e Poço Redondo), whose locations were mapped with the use of a GPS and the individuals were kept in a greenhouse, composing a Active Germplasm Bank (AGB). For molecular analyzes young leaves were collected and used for DNA extraction. Eleven ISSR primers and 13 RAPD primers were used to characterize the prospected accessions. Analyses by flow cytometry were performed for the determination of DNA content, using young leaves and extraction of nuclei was performed following the method of Dolezel. ISSR and RAPD markers detected large genetic variability among the accessions of the AGB. The estimation of the DNA content obtained by flow cytometry of the bromeliad accessions collected in four municipalities of Sergipe State allowed the distinction of two groups (group 1 = 1,59 pg and group 2 = 1,057 pg).